The global biogeography of lizard functional groups. (19th July 2019) - Vidan, Enav; Novosolov, Maria; Bauer, Aaron M.; Herrera, Fernando Castro; Chirio, Laurent; de Campos Nogueira, Cristiano; Doan, Tiffany M.; Lewin, Amir; Meirte, Danny; Nagy, Zoltan T.; Pincheira‐Donoso, Daniel; Tallowin, Oliver J.S.; et al.
Abstract: Aim: Understanding the mechanisms determining species richness is a primary goal of biogeography. Richness patterns of sub‐groups within a taxon are usually assumed to be driven by similar processes. However, if richness of distinct ecological strategies respond differently to the same processes, inferences made for an entire taxon may be misleading. We deconstruct the global lizard assemblage into functional groups and examine the congruence among richness patterns between them. We further examine the species richness – functional richness relationship to elucidate the way functional diversity contributes to the overall species richness patterns. Location: Global. Methods: Using comprehensive biological trait databases we classified the global lizard assemblage into ecological strategies based on body size, diet, activity times and microhabitat preferences, using Archetypal Analysis. We then examined spatial gradients in the richness of each strategy at the one‐degree grid cell, biome, and realm scales. Results: We found that lizards can best be characterized by seven "ecological strategies": scansorial, terrestrial, nocturnal, herbivorous, fossorial, large, and semi‐aquatic . There are large differences among the global richness patterns of these strategies. While the major richness hotspot for lizards in general is in Australia, several strategies exhibit highest richness in the Amazon Basin. Importantly, the global maximum in lizard species richness is achieved at intermediate values of functional diversity and increasing functional diversity further result in a slow decline of species richness. Main conclusions: The deconstruction of the global lizard assemblage along multiple ecological axes offers a new way to conceive lizard diversity patterns. It suggests that local lizard richness mostly increases when species belonging to particular ecological strategies become hyper‐diverse there, and not because more ecological types are present in the most species rich localities. Thus maximum richness and maximum ecological diversity do not overlap. These results shed light on the global richness pattern of lizards, and highlight previously unidentified spatial patterns in understudied functional groups.